Implementasi Model Pembelajaran Problem Based Learning melalui Media Puzzle Sipeling dalam Peningkatan Hasil Belajar pada Kompetensi Peduli Lingkungan Siswa Kelas II SD Negeri Lemberang - Utami, Rohyana Felisa; Purwati, Panca Dewi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research was motivated by the low learning outcomes of students in class II of Lemberang State Elementary School, Sokaraja. Based on the results of observations that have been made at the elementary school, specifically in class II, it can be seen that the majority of students have not yet reached the criteria for completion in learning, especially in learning Pancasila and Citizenship Education regarding attitudes and caring for the school environment due to a lack of instilling and implementing caring attitudes towards the environment. The research method used is descriptive qualitative with data collection techniques in the form of observation, pre-test post test, interviews and documentation. From the research conducted, there was an increase in learning motivation for class II students in learning Pancasila Education. This can be seen from the results of the pre-test and post-test which experienced an average increase of 24 from an average of 66 to 90.